2013
DOI: 10.1371/journal.pone.0058498
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associations of Incomplete Posterior Vitreous Detachment in Adult Chinese: The Beijing Eye Study

Abstract: PurposeTo determine prevalence and associations of incomplete posterior vitreous detachment (PVD).MethodsThe population-based cross-sectional Beijing Eye Study 2011 included 3468 individuals with a mean age of 64.6±9.8 years (range: 50–93 years). A detailed ophthalmic examination was performed including spectral-domain optical coherence tomography (SD-OCT). Incomplete PVD was differentiated into type 1 (shallow PVD with circular perifoveal vitreous attachment), type 2 (PVD reaching fovea but not foveola), type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
28
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 23 publications
9
28
1
3
Order By: Relevance
“…This is consistent with an increased prevalence of incomplete PVD in hypermetropia, as previously reported [20]. …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with an increased prevalence of incomplete PVD in hypermetropia, as previously reported [20]. …”
Section: Resultssupporting
confidence: 93%
“…The results of this study did not identify a difference between women and men for the prevalence of VMT due to the limited study cohort. The Beijing Eye Study [20] reported a slightly higher prevalence of VMT of 2.4% in a Chinese population aged >50 years. This prevalence increased with age and was higher in women than in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no published incidence studies of VMT to compare with, but the Beijing Eye study did use OCT to evaluate the completeness of PVD and found a prevalence figure of 2.3% with incomplete PVD. 17 The prevalence of symptomatic VMT in patients with and without coexisting pathology was estimated by Jackson et al 18 to be 0.35%. This discrepancy may not only be due to Jackson et al using combined numbers from smaller trials in tertiary referral centres compared with our general hospital setting but may also be due to the inevitable discrepancy in classification of VMA and VMT.…”
Section: Discussionmentioning
confidence: 97%
“…Aunque la prevalencia [14][15][16][17][18] y la incidencia [19] de los AM en la población general se encuentran bien documentados se disponen de pocos datos sobre la prevalencia de la AVM y la TVM en la población general [20,21] . El diagnóstico de las enfermedades en la IVM a menudo se realiza tan solo en estadios avanzados, cuando los pacientes experimentan la carga de la enfermedad sobre la vista en las últimas etapas de la enfermedad.…”
unclassified